Effectiveness of Online Media on Website of KOMUNITA Magazine - Egi, Abinowi; Aminudin (CENTRAL ASIA AND THE CAUCASUS, 2022)
KOMUNITA Magazine as a means to develop higher education from various aspects. In this regard, KOMUNITA is a medium of communication and information that seeks to reach various communities that intersect with higher education from upstream to downstream. Komunita magazines in online media in the form of websites have now undergone many changes and developments so there needs to be a study to determine the effectiveness of the website. To find out the effectiveness of website changes and development, the author tries to study using google analytics. Google analytics can generate a visitor analysis report from the web, so the authors see the effectiveness based on the number of visitors.